DESAIN DAN EVALUASI PENGGUNAAN MEDIA PEMBELAJARAN MATERI MOMEN INERSIA MENGGUNAKAN ARDUINO - Ridwan Hani; Sri Zakiyah; Dadi Rusdiana (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2023)
The advancement of technology drives various innovations in educational products as support tools for learning activities such as physics. For instance, Arduino, an open-source developmental platform for instructional technology has rapidly applied to all kinds of educational levels. This research aims to design Arduino-based experimental tools for inertia topics and to evaluate the implementation of students. Moreover, we use a one-group pretest-posttest design as a research method. For collecting data, we use objective tests and questionnaires as an instrument. The effectiveness of Arduino-based experimental tools was assessed through posttest dan pretest data by using inferential statistics—Wilcoxon and n-gain. The apparent results show that the implementation of Arduino-based design towards students enhances their understanding of inertia topic with 0,00 and 0,75 for Wilcoxon and n-gain, respectively.